Phosphorylation, compartmentalization, and cardiac function. Issue 4 (8th October 2022) - Collins, Kerrie B.; Scott, John D.
Abstract: Protein phosphorylation is a fundamental element of cell signaling. First discovered as a biochemical switch in glycogen metabolism, we now know that this posttranslational modification permeates all aspects of cellular behavior. In humans, over 540 protein kinases attach phosphate to acceptor amino acids, whereas around 160 phosphoprotein phosphatases remove phosphate to terminate signaling. Aberrant phosphorylation underlies disease, and kinase inhibitor drugs are increasingly used clinically as targeted therapies. Specificity in protein phosphorylation is achieved in part because kinases and phosphatases are spatially organized inside cells. A prototypic example is compartmentalization of the cyclic adenosine 3′, 5′‐monophosphate (cAMP)‐dependent protein kinase A through association with A‐kinase anchoring proteins. This configuration creates autonomous signaling islands where the anchored kinase is constrained in proximity to activators, effectors, and selected substates. This article primarily focuses on A kinase anchoring protein (AKAP) signaling in the heart with an emphasis on anchoring proteins that spatiotemporally coordinate excitation‐contraction coupling and hypertrophic responses.